2015
DOI: 10.1039/c5ta06371j
|View full text |Cite
|
Sign up to set email alerts
|

Copper substituted P2-type Na0.67CuxMn1−xO2: a stable high-power sodium-ion battery cathode

Abstract: Plate-like copper-substituted P2-type Na0.67CuxMn1−xO2 is able to rapidly charge and discharge within 5 minutes while still giving a capacity of about 90 mA h g−1 at a current of 1000 mA g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
111
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 48 publications
8
111
2
Order By: Relevance
“…[101] Interestingly, the Li/Mg substitution and manganese enrichment show an increased operating voltage similar to that observed in Li 2 MnO 3 -based electrodes in LIBs, which may resulted from oxide ion redox activity. [102][103][104] Improved battery performance was also achieved in copper-substituted P2-type Na 0.67 Cu x Mn 1−x O 2 [105] and Aldoped Na 2/3 Mn 1−x Al x O 2 . [106] The other essential for layered Na x MnO 2 materials is to further improve the storage voltage of redox Mn 4+ /Mn 3+ and air stability before a practical application.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[101] Interestingly, the Li/Mg substitution and manganese enrichment show an increased operating voltage similar to that observed in Li 2 MnO 3 -based electrodes in LIBs, which may resulted from oxide ion redox activity. [102][103][104] Improved battery performance was also achieved in copper-substituted P2-type Na 0.67 Cu x Mn 1−x O 2 [105] and Aldoped Na 2/3 Mn 1−x Al x O 2 . [106] The other essential for layered Na x MnO 2 materials is to further improve the storage voltage of redox Mn 4+ /Mn 3+ and air stability before a practical application.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[5a-c] Moreover,f irst-principle calculations have demonstrated that sodium ions in the P2 structure can diffuse directly between two face-sharing trigonal prismatic sites with arare phase transition. [12][13][14][15] However the redox behavior of Cu 2+/3+ in previous reports is inconsistent even for the same material, and little research has been conducted into it.It would therefore be interesting if we can correlate the biphase synergy with cost-effective transition metals. [2,3,[6][7][8] However,a s demonstrated by Victor and co-workers,t he Jahn-Teller effect exhibited by Fe IV can potentially induce structural strain and the insertion of water and carbonate ions.…”
mentioning
confidence: 96%
“…[4a, 5d-f] Fe-and Mn-containing P2 phase layered oxides have been of particular interest since these elements are abundant and nontoxic. [12][13][14][15] However the redox behavior of Cu 2+/3+ in previous reports is inconsistent even for the same material, and little research has been conducted into it. [3,6] Recently,t he biphase synergy in NIBs has been wellillustrated by Guo et al (layered P2/O3 composite) and Hou et al (layered P3/P2 composite).…”
mentioning
confidence: 96%
“…When cycled at 0.5 C, the initial charge and discharge capacities are 171.1 and 152.8 mA h g −1 , corresponding to a Coulombic efficiency of 89.3%. [27,31] The incorporation of Cu into layered oxides can improve the surface structure as well, thus protecting the material from direct contact with air and avoiding oxidization under air. In particular, the electrode delivers 81.6% capacity retention of the first cycle reversible capacity (122.5 mA h g −1 ) over 400 cycles at 1 C, which indicates that electrode has relatively high capacity retention.…”
mentioning
confidence: 99%
“…After 400 cycles, the reversible capacity of 103.0 mA h g −1 is maintained, with capacity retention of 67.4%. [9,27] Although the Na[Li 0.05 Mn 0.50 Ni 0.30 Cu 0.10 Mg 0.05 ]O 2 cathode material delivers excellent electrochemical properties, a slight capacity fading is definitely observed during the long-period cycling. The Coulombic efficiencies during cycling at 0.1, 0.5, and 1 C are close to 100%, apart from in the first cycle.…”
mentioning
confidence: 99%